Konsep Pendidikan Akhlak dan Dakwah dalam Perspektif Dr. KH. Zakky Mubarak, MA - Muchtar, Muchtar; Setiawan, Dede; Bahri, Saiful (Jurnal Studi Al-Qur’an, 2017)
Research aims to understand role, and the concept of education and dakwah in perspective Dr. KH. Zakky Mubarak, MA. This research departs from looking at the phenomenon of human life is increasingly complex, entered the modern life and globalization present and the future, wich is characterized by technical and professional paced lives, is forecast to many people ignore the moral and religious in individual and social life. The concept of moral education in the perspective of Dr. KH. Zakky Mubarak, MA that establishes the character of the learners, provide good role models, develop the moral high level, and then apply the knowledge of good character and exemplary in real life so it can become an ingrained habit. The concept of dakwah in perspective Dr. KH. Zakky Mubarak, MA at least two steps that need to be understood by a preacher, first that of bringing the wisdom, it means explaining the wisdoms contained in worship and other Islamic activities without patronizing impression, meaning a preacher should put the words and appropriate sentence appropriate to the circumstances . The second is to mau’idlah hasanah , means giving advice that touch the heart so that the message can be embedded in the memories of audience. Dr. KH. Zakky Mubarak, MA is one of the Nahdlatul Ulama cleric who spend their time preaching, either through a lecture or through scientific papers, scientific papers written contains a lot of moral education that can be used as a reference. Keywords: Concept of Education and Dakwah, Zakky Mubarak, Nahdlatul Ulama Abstrak Penelitian ini bertujuan untuk mengetahui peran, serta konsep pendidikan akhlak dan dakwah dalam perspektif Dr. KH. Zakky Mubarak, MA. Kesimpulan penelitian ini bahwa Konsep pendidikan akhlak dalam perspektif Dr. KH. Zakky Mubarak, MA yaitu menanamkan pemahaman tentang akhlak terhadap peserta didik, memberikan keteladanan yang baik, mengembangkan pada akhlak tingkat tinggi, dan kemudian mengaplikasikan pengetahuan tentang akhlak dan keteladanan tersebut dalam kehidupan nyata sehingga dapat mengakar menjadi suatu kebiasaan. Sedangkan konsep dakwah dalam perspektif Dr. KH. Zakky Mubarak, MA paling sedikit ada dua langkah yang perlu dipahami oleh seorang pendakwah, pertama yaitu menyampaikan dengan hikmah, kedua adalah dengan mauâ€™idlah hasanah, artinya memberikan nasehat-nasehat yang menyentuh kalbu sehingga pesan yang disampaikan dapat melekat dalam ingatan objek dakwah (madâ€™u). Kata Kunci: Konsep Pendidikan Akhlak, Dakwah, Zakky Mubarak